Modelling of an autoclave used for high pressure sulphuric acid/oxygen leaching of first stage leach residue. Part 1: Model development - Dorfling, C; Akdogan, G.; Bradshaw, S; Eksteen, Jacques (Elsevier, 2013)
Pressure leaching of the first stage leach residue in Base Metal Refinery (BMR) circuits aims to achieve high base metal dissolution with minimal precious metal leaching. Optimum autoclave operation is challenging because of the complex leaching chemistry, varying mineralogy of the feed material, and interaction between the different process variables. This research involved the modelling of the pressure leaching stages with flash recycle cooling at a typical BMR. The steady state solution employed the sequential modular approach in MATLAB, while the dynamic simulation involved the simultaneous solution of a set of differential equations, derived from mass and energy balances, in MATLAB. Part I of this communication presents a discussion of the Western Platinum Ltd. BMR process, an overview of relevant literature, and the strategies followed to develop both a steady state model and a dynamic model. Part II of this communication discusses the application of the models.